Bioactive polyurethane ureas with physically immobilized folate-ferrocene conjugate - Makeieva, L. V.; Gladyr, I. I.; Roznova, R. A.; Galatenko, N. A.; Zakashun, T. U.; Gryzenko, V. P. (Reports of the National Academy of Sciences of Ukraine, 2014)
New polyurethane ureas based on polyoxypropylene glycol and 2,4-,2,6-toluene diisocyanate, using diamines (1,6-hexamethylenediamine or 4,4′-diaminodiphenylmethane) as chain extenders and physically immobilized folate-ferrocene conjugate, are synthesized. IR-spectroscopic, physical, and mechanical investigations are carried out. Pharmacokinetic studies of the prolonged form of folateferrocene conjugate, contained in polyurethane ureas, testify to the bioactivity of the obtained polymeric materials.